THE RISK OF PREMATURE VENTRICULAR CONTRACTIONS DEPENDING ON PARAMETERS OF THE LEFT VENTRICULAR SYSTOLIC FUNCTION AMONG PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Sid, E. V.; Malynovska, O. Ya. (Modern medical technology, 2019)
Despite the preventive measures taken to reduce the incidence of coronary heart disease, cardiovascular diseases remain the leading cause of death. In patients with acute myocardial infarction ventricular arrhythmias can be an important prognostic factor. Identifying of premature ventricular contractions (PVCs) predictors and stratifying the risk of life-threatening arrhythmias development are a complex clinical task. Purpose of the study. To determine the relative risk of premature ventricular contractions depending depending on the parameters of the left ventricular systolic function among patients with acute myocardial infarction. Material and methods. The results of the study are based on the data obtained from a comprehensive examination of 120 patients after STEMI: with premature ventricular contractions (86 patients) and without premature ventricular contractions (34 patients). Screening of patients was carried out at the base of Municipal institution «Regional medical center of cardiovascular diseases» of Zaporizhzhia Regional Council in the period from 2016 to 2017. All examined persons were comparable by age, social status and sex (the ratio of men to women was 4 to 1). Results and discussion. The largest area under the ROC curve (AUC = 0,76, 95% CI 0,668 to 0,829) among the analyzed parameters of systolic heart function had an indicator of the left ventricle ejection fraction (LF EF). At the cut-off point < 54,2% sensitivity was 57,0% and specificity 85,3%. In the group with STEMI and PVCs were 50 patients with LF EF below 54,2% and 36 ones above 54,2%, in the group STEMI without PVCs, 6 patients had LF EF below 54,2% and 28 ones had LF EF above 54,2% respectively. Relative risk was 1,59, 95% CI 1,26–2,01.